Խալյուբների նույնականացման և տեղադրության հարցի շուրջ - Խորիկյան, Հովհաննես (ԱրՊՀ հրատ․)
Анализ источников показывает, что древние авторы под названием халибы имеют ввиду разные племена, занимающиеся металообработкой. При этом, восточные халибы идентифицировались с мосхами, которые были иранским племенем и локализировались на землях в нижнем течении р. Чорох до р. Кура. The investigation of sources shows that the ancient authors accepted different tribes dealing with metallurgy under the name of Chalibyans. Therefore the Eastern Chalibyans are identified with the Moschians, being an Iranian tribe and living in the lands that stretch from the lower stream of the Çoroh River to the Cyrus River.
Keywords: Պատմություն; Տեղագրություն; Արցախ